Studi Kompleks Assosiasi Pb (II) Dengan Penambahan KI dan Rhodamin B - Muhammad Satrio Hutomo; Edi Nasra; Syamsi Aini; Hesty Parbuntari (Jurnal Periodic Jurusan Kimia UNP, 2023)
Abstract — Research has been carried out on the study of the Pb(II) association complex using KI and Rhodamine B. This study aims to find the optimum conditions for the Pb(II) association complex such as iodine concentration, solution pH, and Rhodamine B concentration. The measurement method used is the UV spectrophotometry method. -Vis and AAS (Atomic Absorption Spectrophotometer). Pb(II) is reacted with excess iodine to form an anion complex (PbI4)2-. The anion complex formed is then reacted with a Rhodamine B cation complex (RB+ ) to form an association complex [RB]2[PbI4]. The results showed that the optimum condition of iodine for the formation of the anion complex (PbI4)2-  at a time of 2 hours, a concentration of 0.4 M with an absorbance of 0.1069 A at a maximum wavelength of 266 nm. While the optimum conditions for the association complex [RB]2[PbI4]2- occurred at a wavelength of 555 nm with an absorbance of 0.3348 A, pH 5 with an absorbance of 3.4101 A and a concentration of Rhodamine B 0.001% with an absorbance of 2.2798 A. The resulting association complex contacted with Pb(NO3)2- at a concentration of 0.01 ppm succeeded in concentrating by obtaining a concentration of 0.7419 ppm and an absorbance value of 0.0108 A. So that a concentration factor of 74.19 times was obtained.